2021
DOI: 10.1177/15593258211013655
|View full text |Cite|
|
Sign up to set email alerts
|

Optimization of Thymoquinone-Loaded Self-Nanoemulsion for Management of Indomethacin-Induced Ulcer

Abstract: To improve the water solubility of thymoquinone (TQ), a major constituent of Nigella sativa seed oil, a TQ-loaded self-nanoemulsifying drug delivery system (SNEDDS) was prepared. The SNEDDS formulation was optimized using almond oil (AO) (Oil; X1), tween 80 (surfactant; X2) and polyethylene glycol 200 (PEG 200) (cosurfactant; X3) compounds as independent variables. The results showed that the globule size ranged from 65 to 320 nm. In addition, a strong agreement was reached between the system estimation and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that thymoquinone (TMQ), a major constituent of black seed oil (BSO), possesses gastroprotective effects and can help treat peptic ulcers more potently when formulated using a SNEDDS-based delivery approach [17]. Additional research found BSO to be more effective than TMQ alone for reducing peptic ulcer indices in animal models [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that thymoquinone (TMQ), a major constituent of black seed oil (BSO), possesses gastroprotective effects and can help treat peptic ulcers more potently when formulated using a SNEDDS-based delivery approach [17]. Additional research found BSO to be more effective than TMQ alone for reducing peptic ulcer indices in animal models [14].…”
Section: Discussionmentioning
confidence: 99%
“…Furtherm et al prepared a TMQ-loaded SNEDDS to study the impact of increasing dr on the therapeutic effects. Their study reported that the formulated TMQ-S creased the ulcer index by 2-fold compared to free TMQ alone, as indicated ings [17]. Despite their reported in vivo activity, the FDA has not yet approve extracts or concentrated thymoquinone for treating any medical conditions l lesterol, diabetes, or high blood pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…207 Similarly, to investigate the gastroprotective effect in a rat model, in silico response and contour plots have been used to optimize the globule size of self-nano emulsion particles, where the predicted sizes were similar to the actual value measured (67.7 nm calculated versus 64.8 nm actual). 208 Adding automation for the high throughput screening of nanoparticle formulations is necessary to improve optimization speed and predict biological interactions such as solubility and potential penetration capabilities. 209,210 3.3.1.…”
Section: Nm Design Strategies and Surface Engineeringmentioning
confidence: 99%